Bangla Version of the Shoulder Pain and Disability Index (SPADI): Translation, Cross-Cultural Adaptation, Validation and Reliability Assessment - Rahman, Hasan Habibur; Hasan, Md Israt; Uddin, Taslim; Saha, Tulshi Chandra; Hojaifa, Musa Muhammad; Sadeque, ABM Zafar (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Shoulder pain comes next to back and knee pain, considering the frequency of musculoskeletal ailments. The Shoulder Pain and Disability Index (SPADI) is considered a highly specific questionnaire for assessing shoulder pain and functions. The objective of the study was to assess the validity and reliability of the Bangla version of SPADI (B-SPADI) among the Bangla-speaking patients. Materials and methods: The B-SPADI was developed using a designed process that included forward translation and backward translation, authentication, response, and final rectification. Validity and reliability were conducted in 48 patients with shoulder pain. The reliability was appraised by executing internal consistency and test-retest analyses. Its validity was assessed by comparing the SPADI with the SF- 36, Disabilities of the Arm, Shoulder, and Hand (DASH), and American Shoulder and Elbow Surgeons (ASES) questionnaire. Results: The cross-cultural adaptation method was flawlessly aligned with the content or language. Internal consistency (Cronbach’s alpha) was 0.97 for the total SPADI score. Intraclass Correlation Coefficient (ICC) was 0.95 for the total SPADI with 0.92 for pain subtotal and 0.96 for disability subtotal. The SPADI total score showed a correlation of 0.63–0.71 with the SF-36 physical scales, of 0.89 with the DASH and of 0.94 with the ASES. All of the items were statistically significant (P<0.001). Conclusion: The B-SPADI came out as an appropriate valid, and reliable instrument for measuring pain and disability in patients with shoulder afflictions. J Bangladesh Coll Phys Surg 2022; 40: 159-165